2015
DOI: 10.5603/ep.a2016.0065
|View full text |Cite
|
Sign up to set email alerts
|

Hormon anty-müllerowski i zespół policystycznych jajników

Abstract: Anti-Müllerian hormone (AMH) is a glycoprotein, a member of the transforming growth factor β family, reflecting the number of ovarian antral follicles. Polycystic ovary syndrome (PCOS) is a common endocrinopathy predisposing to infertility, and metabolic and cardiovascular complications. In our review, we discuss the role of AMH in PCOS pathophysiology and its clinical applications according to the published studies. Improvement of AMH assay validity will allow the clinical utility of this valuable biomarker t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Additionally, we found impaired glucose metabolism in L/L group of rats, which was consistent with manifestation of PCOS in patients (Dumont et al, 2015;Łebkowska and Kowalska, 2017). Lower basal insulin level and HOMA-β indicated poorer β-cell secretion and function after continuous light exposure.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, we found impaired glucose metabolism in L/L group of rats, which was consistent with manifestation of PCOS in patients (Dumont et al, 2015;Łebkowska and Kowalska, 2017). Lower basal insulin level and HOMA-β indicated poorer β-cell secretion and function after continuous light exposure.…”
Section: Discussionsupporting
confidence: 81%
“…AMH levels start to rise by much as 17% three years before puberty and declines by 30% within the first 2 years of puberty. Several studies have reported higher AMH levels in women with PCOS [35-37]. Crisosto et al [38] showed higher (AMH) levels in prepubertal and peripubertal daughters of PCOS women, suggesting that these girls may have an altered follicular development which starts early in development and continues through puberty.…”
Section: Discussionmentioning
confidence: 99%
“…In PCOS diagnostics, determination of anti-Mullerian hormone (AMH) is not recommended due to lack of standardisation and low sensitivity of this method, and due to no cut-off value accepted as a standard [2,12]. AMH concentrations in the group of PCOS women are higher than in the group of healthy women and are well correlated with antral follicles in an ovary [28]. The concept was postulated in PCOS diagnosis to apply AMH concentration convertible with the number of antral follicles found in ultrasound examination.…”
Section: Clinical and Biochemical Characteristics Of Hyperandrogenismmentioning
confidence: 99%